Species of the genus Limnellia from China (Diptera: Ephydridae) - Zhang, Junhua; Yang, Ding (Zootaxa, 2009)
The genus Limnellia Malloch is recorded from China as well as the Oriental region for the first time. Two new species, Limnellia flavitarsis sp. nov. and L. luchunensis sp. nov., are described, and two species, L. stenhammari (Zetterstedt) and L. maculipennis Malloch, are recorded from China for the first time. A key of the genus Limnellia from China is presented.